2021
DOI: 10.1002/prp2.778
|View full text |Cite
|
Sign up to set email alerts
|

Histamine in cancer immunology and immunotherapy. Current status and new perspectives

Abstract: Cancer is the second leading cause of death globally and its incidence and mortality are rapidly increasing worldwide. The dynamic interaction of immune cells and tumor cells determines the clinical outcome of cancer. Immunotherapy comes to the forefront of cancer treatments, resulting in impressive and durable responses but only in a fraction of patients. Thus, understanding the characteristics and profiles of immune cells in the tumor microenvironment (TME) is a necessary step to move forward in the design o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 373 publications
(377 reference statements)
0
15
0
Order By: Relevance
“…Studies of the effects of tissue-infiltrating mast cells on several other types of cancers have indicated that mast cells can play progressive as well as inhibitory roles depending on tumor microenvironment. 31 In human bladder cancer, histological grade positively correlated with mast cell density, and mast cells promoted cancer progression by stimulating estrogen receptor (ER) in mice. 32,33 In human breast cancer, mast cell counts were higher with favorable molecular subtypes, including luminal A and luminal B; however, the correlation between the number of ER-positive cancer cells and mast cells in high-grade tumors suggested that ER stimulation by mast cells might play a role in breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the effects of tissue-infiltrating mast cells on several other types of cancers have indicated that mast cells can play progressive as well as inhibitory roles depending on tumor microenvironment. 31 In human bladder cancer, histological grade positively correlated with mast cell density, and mast cells promoted cancer progression by stimulating estrogen receptor (ER) in mice. 32,33 In human breast cancer, mast cell counts were higher with favorable molecular subtypes, including luminal A and luminal B; however, the correlation between the number of ER-positive cancer cells and mast cells in high-grade tumors suggested that ER stimulation by mast cells might play a role in breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the effects of tissue‐infiltrating mast cells on several other types of cancers have indicated that mast cells can play progressive as well as inhibitory roles depending on tumor microenvironment 31 . In human bladder cancer, histological grade positively correlated with mast cell density, and mast cells promoted cancer progression by stimulating estrogen receptor (ER) in mice 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, HA-loaded formulations (GS-HA and GS-PTX-HA) reduced neovascularization, a vital process for tumor growth, reinforcing the HA-induced inhibition of cell growth and antiangiogenic effect we had previously demonstrated in 4T1 tumors [ 16 ]. Furthermore, considering that HA dihydrochloride has been used as an adjuvant to IL-2 immunotherapy with proven clinical benefit in acute myeloid leukemia [ 50 , 51 ], it is important to point out that the GS-HA nanoformulation produced comparable antitumoral and antiangiogenic responses at the administered doses when compared to the chemotherapeutic-loaded micelles, highlighting the feasible therapeutic exploitation of this biogenic amine. The use of a system that involves an endogenous molecule provides a promising new approach for TNBC treatment with numerous advantages over chemotherapy in terms of short and long-term toxicity, and the therapeutic costs associated with the drug production and access to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently four histamine receptors: H1, H2, H3, H4. They are named respectively according to the order in which they were discovered [15]. The enzyme responsible for histamine production is histidine decarboxylase (HDC).…”
Section: Mechanism Of Action Of Histamine and Its Receptorsmentioning
confidence: 99%